Social Construction of Quality Family Village Pondok Batu Village, Bilah Hulu Subdistrick, Labuhanbatu Regency - Ira Maya Sofa Harahap; Badaruddin Badaruddin; Muba Simanihuruk; Hadriana Marhaeni Munthe; T. Ilham Saladin (LPPM Universitas PGRI Sumatera Barat, 2024)
The Social Construction of the Quality Family Village in Pondok Batu Village, Bilah Hulu Subdistrict, Labuhanbatu Regency is a strategic effort to improve the quality of life in the community through a participatory approach. This study aims to analyze how the community constructs their social reality in the context of the Quality Family Village program, using the social construction theory perspective of Peter L. Berger. The research method employed is qualitative, with data collection through interviews, observations, and documentary studies. The results show that the processes of externalization, objectivation, and internalization are key in building the community's collective awareness of the importance of this program. The community plays an active role in formulating and implementing programs relevant to their needs, thereby creating new norms that support the improvement of quality of life. Furthermore, this study also identifies the challenges faced in the program's implementation, including a lack of understanding and participation from some segments of the community. Therefore, further efforts are needed to enhance the socialization and education about the Quality Family Village program in order to achieve the expected goals.